ECONOMIC SECURITY OF CREDIT UNIONS IN UKRAINE - Yehorycheva , Svitlana (Socio-economic relations in the digital society, 2021)
Abstract. The purpose of the article is to determine the content of economic security of credit unions andthreats that provoke a decrease in its level, as well as analysis of the current state of the COP in terms of ensuringtheir economic security. The content of the concept of credit unions’ economic security as the protection of theireconomic interests arising from the cooperative nature of such unions from threats that may prevent the efficientuse of all their resources to achieve the goal of creating — the fullest meeting of financial needs of the membersowners,is investigated. External political, socio-economic, regulatory and legal, technical, informational andother threats to the functioning of credit unions are highlighted. Emphasis is placed on the special importancefor ensuring their economic security of the institutional environment, which, at the same time, is capable of generatingregulatory and legal threats. The reasons why credit unions were the most vulnerable to quarantinerestrictions have been identified. The internal threats generated by the functioning of credit unions, on theone hand, as organizations, and on the other hand — as financial intermediaries, are analyzed. The conclusionis made that credit unions, which really adhere to the cooperative principles of organization and functioning,have the potential for development.It has been proven that credit unions, despite the serious problems of modern development, have alreadybecome an integral part of the financial sector of Ukraine. Those of them who really adhere to the cooperativeprinciples of organization and functioning, have their own market niche and are able to restore developmentpotential. The economic security of credit unions is determined by the protection of their economic interests,which consist in the fullest satisfaction of the financial needs of their member members. It is possible to guaranteesuch a state to credit unions, first of all, by improving the legal framework of their activities, which shouldcomprehensively reflect the cooperative nature of these institutions.Keywords: credit union, credit cooperative, economic security, threat, non-profit organization, regulation.JEL Classification G21Formulas: 0; fig.: 2; tabl.: 2; bibl.: 28.
Keywords: credit union; credit cooperative; economic security; threat; non-profit organization; regulation